100 PRIMEROS MIEMBROS DE LA SOCIEDAD ESPAÑOLA PARA EL ESTUDIO DE LOS PASTOS (S.E.E.P.) - Pastos, Editor (Pastos, 2011)
100 PRIMEROS MIEMBROS DE LA SOCIEDAD ESPAÑOLA PARA EL ESTUDIO DE LOS PASTOS (S.E.E.P.)